The complete chloroplast genome of Aristolochia kwangsiensi - Qiang Zhou; Jingling Li; Mei Jiang; Liqiang Wang; Chang Liu; Yuhua Wang (Mitochondrial DNA. Part B. Resources, 2020)
Aristolochia kwangsiensis belongs to Aristolochiaceae family that has many genotoxic plants. Here, we sequenced the complete chloroplast genome of A. kwangsiensis. The genome is 159,849 bp in size with a pair of inverted repeats of 25,570 bp, a large single-copy region of 70,457 bp, and a small single copy region of 19,315 bp. The genome encodes 106 unique genes, including 76 protein-coding, three rRNA, and 27 tRNA genes. Phylogenomic analysis shows that A. kwangsiensis and A. kunmingensis and A. moupinensis form a sister clade. These results will help further studies on taxonomy, phylogeny and evolution of Aristolochiaceae family.